PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM UPAYA PENCEGAHAN PENYEBARAN VIRUS COVID-19 PADA AREA KERJA PT. SEMEN PADANG - Ratu Mira Ferial (Journal of Education on Social Science (JESS), 2020)
The Ministry of State Owned Enterprises has issued a circular decree number S-336/MBU/05/2020 asking all SOE President Directors to prepare anticipation for the scenario of “The New Normal” starting from May 25, 2020. As a follow-up the circular decree, PT. Semen Padang has carried out efforts to overcome the spread of the Covid-19 virus in the work area of PT. Semen Padang by forming the Covid-19 Team. This research aimed to determine how the occupational safety and health (K3) program was implemented in an effort to prevent the spread of the covid-19 virus in the work environment of PT. Semen Padang. This research was a descriptive qualitative with case study method. Data collection techniques used in this study were interviews and documentation. Resource persons are determined by non-probability sampling and the technique used is purposive sampling. The results showed that PT. Semen Padang has formed a Covid-19 Team which has established the Working Guidelines for The New Normal Conditions. This work guide contains several modules which must be obeyed by all employees and other parties related to PT. Semen Padang, including the work module, the WFH module, the meeting module, the official travel module, the food/ drink module, the prayer module, the wearing mask module, the driving module, the corporate public facility usage module, the cleaning officer module and security module.